PENGARUH GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA DAN HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS III SD NEGERI SIDOKUMPUL - Eldy Maharinda; Putri Racmadayanti; Amalia Rahmawati (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the effect of the School Literacy Movement on interest in reading and learning outcomes of Indonesian Language in grade III students of SD Negeri Sidokumpul 2022/2023 Academic Year. This research is a quasi-experimental study with The Posttest-Only Control-Group Design. The study population was all students in grade III Elementary School I Teacher for 2022/2023 Academic Year, 60 students. In determining the sample is done by using random sampling techniques, it was found that: class III B as the experimental group, while class III C as the control group. Data on reading interest was collected by questionnaire and students' learning outcomes in Indonesian used a multiple choice test. Data were analyzed using Manova analysis assisted by SPSS 17.00 for windows. The results showed that: First, there was a significant influence on the School Literacy Movement on the interest in reading Indonesian in grade III students of SD Negeri Sidokumpul, East Sidoarjo District, 2022/2023 Academic Year. Second, there is a significant influence on the School Literacy Movement on the learning outcomes of Indonesian Language in thirth grade students of SD Negeri Sidokumpul District in 2022/2023 Academic Year. And thirdly, there is a significant influence on the School Literacy Movement on interest in reading and learning outcomes in Indonesian Language in grade III students of SD Negeri Sidokumpul District in 2022/2023 Academic Year.